2015
DOI: 10.1159/000430139
|View full text |Cite
|
Sign up to set email alerts
|

Periostin Mediates TGF-β-Induced Epithelial Mesenchymal Transition in Prostate Cancer Cells

Abstract: Background: In our previous study, we found that periostin was upregulated in prostate cancer, and its expression could be modulated by TGF-β. TGF-β could upregulate periostin expression in some cells, and both TGF-β and periostin could induce epithelial mesenchymal transition (EMT). We aimed to study the effect of periostin in the process of TGF-β-induced EMT in prostate cancer cells. Methods: We constructed a lentivirus vector containing the periostin gene and transduced it into PC3 and DU145 cells. After co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
61
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 29 publications
6
61
0
Order By: Relevance
“…Both apoptotic and EMT responses to TGF-β treatment in PC3 and DU145 prostate cancer cells has been observed in separate studies [49][50][51], which suggests that a concomitant apoptosis and EMT may also occur in response to TGF-β in these cells. In the concomitant apoptosis and EMT, accumulating data have shown that the extent of both events can be modulated by either pro-survival and/ or pro-apoptotic factors.…”
Section: Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 68%
See 1 more Smart Citation
“…Both apoptotic and EMT responses to TGF-β treatment in PC3 and DU145 prostate cancer cells has been observed in separate studies [49][50][51], which suggests that a concomitant apoptosis and EMT may also occur in response to TGF-β in these cells. In the concomitant apoptosis and EMT, accumulating data have shown that the extent of both events can be modulated by either pro-survival and/ or pro-apoptotic factors.…”
Section: Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 68%
“…Nevertheless, it is becoming more evident that TGF-β-induced apoptosis is associated with its induction of EMT in normal cells. For instance, as mentioned previously, TGF-β-induced apoptosis concomitantly occurs with EMT in hepatocytes, breast cells, renal cells, and prostate cells [33,34,37,38,[44][45][46][47][48][49]. TGF-β can induce EMT without an apoptotic response in many cancer cells, including pancreatic cancer cells [53][54][55] and lung cancer cells [56][57][58], and in immortal non-cancer cell lines such as Mv1Lu [31,32], MDCK [35,59], MCF10A [43], and HMEC [60].…”
Section: Tgf-β-induced Concomitant Apoptosis and Emtmentioning
confidence: 96%
“…21 An increasing number of studies have shown that periostin over-expression presents in various malignant tumors and closely relates with disease progression. In vitro and in vivo researches demonstrated that periostin participate in key processes in cancer metastasis such as cancer stem cell maintenance, 22 tumor cell survival, 5 protumoral macrophages recruitment, 23 pre-metastatic niche formation, 24 epithelial mesenchymal transition (EMT), 25 and angiogenesis. 26 Increased periostin levels have been detected in serum of patients with some malignant tumors.…”
Section: Discussionmentioning
confidence: 99%
“…2 Our previous study showed that POSTN could induce EMT of prostate cancer cells through PI3K/Akt/ GSK-3 beta signaling pathways. 16 In RCC, POSTN was elevated in stromal fibroblasts and enhanced ccRCC cell attachment. 17 However, the involvement of POSTN in other biological processes such as migration and invasion of RCC is still unclear.…”
Section: Introductionmentioning
confidence: 98%